FABRICATION AND EVALUATION OF CHLORHEXIDINE GLUCONATE-INCORPORATED CHITOSAN-POLY (VINYL ALCOHOL) HYDROGEL FILMS FOR INFECTED WOUNDS - Khin Cho Aye; Sahatsapan, Nitjawan; Panomsuk, Suwannee; Nattapulwat, Nattawat; Aumklad, Porawan; Patrojanasophon, Prasopchai; Pornpitchanarong, Chaiyakarn (Thai Bulletin of Pharmaceutical Sciences, 2023)
Antibacterial dressings play an essential role in wound repair and infection control. This study aimed to fabricate chlorhexidine gluconate (CHX)-loaded chitosan-based hydrogel films via a physical cross-linking approach. Chitosan (2 %w/v) and polyvinyl alcohol (10 %w/v) (2:3 w/w) hydrogels were prepared by repeated freeze-thaw cycles. The drug loading was performed by direct incorporation of the CHX into the polymer solution during the gelation process. The content of CHX loaded in the hydrogel matrix was observed to be 4.45 mg per gram of hydrogel, which is 89.01 ± 7.05% of the initial amount added. The interconnected and porous structure of hydrogels was achieved with a high water content and a good swelling index. The physicochemical properties, drug loading, drug release profile, and antimicrobial activity of the hydrogels were investigated. The hydrogels with excellent physical and mechanical properties were obtained. The release of CHX from the hydrogels was biphasic, with an initial rapid release followed by a gradual release that reached approximately 85% at 24 h. Furthermore, the CHX-loaded hydrogel films displayed effective antibacterial activity against Staphylococcus aureus and Escherichia coli with an inhibition zone of 18 mm and 12 mm, respectively. Therefore, this drug-loaded chitosan-based hydrogel may be a promising antibacterial dressing for wound care.